Prospects for the Digitization of the Energy Sector in Russia - Olga PYATAEVA; Valentina BRITVINA; Alexander ANISIMOV; Irina ANDROSOVA; Oleg SKRYABIN (Communications of International Proceedings, 2021)
The article gives an overview of the current state of energy sector and the relevance of the application of innovative technologies in energy enterprises. The authors consider the main provisions of Energy strategy of Russian Federation, and the groups of problems of innovative development in this sector. In this regard the authors analyze the data on innovation activity of key enterprises of the industry in 2017-2020 and then describe the innovative technologies planned for use in power plants including digital technologies and the main trends in energy innovation. As a conclusion the authors formulate an expert opinion on how to solve the problems identified on the basis of digital technologies.
Keywords: Energy Sector; Innovation; Alternative Energy; Smart Networks; Digital; Smart Grid; Smart Networks; Digitalization.